Formulation of Strategies for Human Resource Competency Development in the Digital Era - Sentot E Baskoro; Dany Luqyana Idris; Muhamad Sigid Safarudin; Bambang Bambang; Faizal Faizal (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to formulate a strategy for developing human resource (HR) competencies in the digital era, characterized by the rapid development of information and communication technology. These changes require HR to possess adaptive, innovative competencies, and the ability to master digital skills. However, in practice, there is still a skills gap between existing capabilities and the needs of the workplace, and the development methods implemented by organizations are suboptimal. This study used a qualitative, descriptive approach. Data were collected through interviews, observation, and documentation, with informants selected using purposive sampling. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing, and its validity was tested through triangulation of sources and methods. The results of the study indicate that a comprehensive HR competency development strategy in the digital era requires competency mapping, the implementation of digital-based learning, strengthening leadership roles, and building a culture of continuous learning.